Pengaruh Derajat Keasaman (pH) Air Laut Terhadap Konsentrasi Kalsium dan Laju Pertumbuhan H A L I M E D A SP - Rukminasari, Nita; Nadiarti, Nadiarti; Awaluddin, Khaerul (Torani Journal of Fisheries and Marine Science, 2014)
Ocean acidification afected marine organisms especially calcifying organisms, such as Halimeda sp. This study was conducted on June to September 2012 at laboratory of Research Center and Development for Marine, Coastal and Small Islands, Hasanuddin University. The aim of study  to determine the efect of acidic level on Calcium concentration and growth rate of calcifying macroalgae, Halimeda sp. The experiment design was used completely  random  design  with  three  treatments  and  three  replicates.  Analysis  variance  was  used  for  data analysis with advanced respon test. Tukey test was used to compare the diference between treatments. Water quality parameters were analyzed descriptively. The results showed that there was a significant diference of pH treatments on calcium concentration an d growth rate of Halimeda sp. The highest calcium concentration was found  at pH 8. In  conclusion, increasing pH level of media disturbed the calcifying  process of Halimeda  sp especially at pH level of 6, while growth rate of Halimeda sp was not afected wit h the decreasing of pH.